2009
DOI: 10.1139/y09-057
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of H+-ATPases in MDCK-C11 cells by aldosterone and vasopressin

Abstract: The objective of the present work was to characterize the biochemical activity of the proton pumps present in the C11 clone of Madin-Darby canine kidney (MDCK) cells, akin to intercalated cells of the collecting duct, as well as to study their regulation by hormones like aldosterone and vasopressin. MDCK-C11 cells from passages 78 to 86 were utilized. The reaction to determine H+-ATPase activity was started by addition of cell homogenates to tubes contained the assay medium. The inorganic phosphate (P(i)) rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 77 publications
3
5
0
Order By: Relevance
“…This stimulatory effect we observed is only due to aldosterone since in the presence of ethanol alone (1-h preincubation), in a similar concentration we used to prepare the hormonal solution, the basal pH i and the pHirr were not different from the control values. Our present results are in accordance with data indicating that aldosterone (10 Ϫ8 M for 24 h) increases H ϩ -ATPase activity in MDCK-C11 cells (7) and that this hormone (10 nM, 15-min preincubation) causes a rapid stimulatory effect on H ϩ -ATPase activity in isolated outer medullary collecting ducts (38) and increases the activity of vacuolar H ϩ -ATPase in turtle urinary bladder (1). However, the present study is the first demonstration, to our knowledge, that aldo- Values are means Ϯ SE; N/n ϭ the no.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This stimulatory effect we observed is only due to aldosterone since in the presence of ethanol alone (1-h preincubation), in a similar concentration we used to prepare the hormonal solution, the basal pH i and the pHirr were not different from the control values. Our present results are in accordance with data indicating that aldosterone (10 Ϫ8 M for 24 h) increases H ϩ -ATPase activity in MDCK-C11 cells (7) and that this hormone (10 nM, 15-min preincubation) causes a rapid stimulatory effect on H ϩ -ATPase activity in isolated outer medullary collecting ducts (38) and increases the activity of vacuolar H ϩ -ATPase in turtle urinary bladder (1). However, the present study is the first demonstration, to our knowledge, that aldo- Values are means Ϯ SE; N/n ϭ the no.…”
Section: Discussionsupporting
confidence: 93%
“…The present data are compatible with our recent demonstration of an aldosterone nongenomic (15-or 1-min preincubation) and genomic (l-h preincubation) effect on the Na ϩ /H ϩ exchanger in S2 (25) and S3 (19) segments of rat proximal tubule. The genomic aldosterone-induced regulation of the H ϩ -ATPase seems to be a mineralocorticoid specific effect, since our data showed that spironolactone inhibits the aldosterone (1-h preincubation) effect on H ϩ -ATPase, as had been observed in MDCK-C11 cells (7). The present results are in accordance with our finding of MR in the S3 segment by RT-PCR (19).…”
Section: Discussionsupporting
confidence: 93%
“…These early studies showed that aldosterone stimulated H + secretion independently of Na + transport as a result of trafficking of proton pumps stored in cytosolic vesicles into the apical membrane of intercalated cells via a PKCdependent signaling pathway (94). Morphological changes in intercalated cell number and apical membrane area were also found to be a (96). The sensitivity of the aldosterone effect to spironolactone in the MDCK cell line would indicate a genomic pathway.…”
Section: Rapid Modulation Of Namentioning
confidence: 84%
“…The observed body weight gain in DOCP-treated mice is consistent with the known effect of DOCP to enhance Na ϩ and fluid volume retention. By the fourth day, DOCP treatment resulted in hypernatremia, an effect that started to wane by 8 …”
Section: Docp Caused Disturbances In Namentioning
confidence: 99%